2015
DOI: 10.4238/2015.may.18.14
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Genome-wide association with residual body weight gain in Bos indicus cattle

Abstract: ABSTRACT. Weight gain is a key performance trait for beef cattle; however, attention should be given to the production costs for better profitability. Therefore, a feed efficiency trait based on performance can be an interesting approach to improve performance without increasing food costs. To identify candidate genes and genomic regions associated with residual body weight gain (RWG), we conducted a genome-wide association study (GWAS) with 720 Nellore cattle using the GRAMMAR-Gamma association test. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…The gene ankrd10a has been detected as a candidate gene for abdominal fat yield on GGA3 in chicken [47]. The gene iffo2 has been associated with residual body weight gain in cattle [48]. The apoer2 (also known as low-density lipoprotein receptor-related protein 8, lrp8 ) is a member of the low density lipoprotein receptor (LDLR) gene family, which is not only involved in the lipid metabolism, but also plays an important role in endocytosis and signal transduction [49].…”
Section: Discussionmentioning
confidence: 99%
“…The gene ankrd10a has been detected as a candidate gene for abdominal fat yield on GGA3 in chicken [47]. The gene iffo2 has been associated with residual body weight gain in cattle [48]. The apoer2 (also known as low-density lipoprotein receptor-related protein 8, lrp8 ) is a member of the low density lipoprotein receptor (LDLR) gene family, which is not only involved in the lipid metabolism, but also plays an important role in endocytosis and signal transduction [49].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal pancreatic function could conceivably affect weight gain, though a role for LNX2 in the gut or in regulating some aspect of metabolism could also be responsible. Interestingly a genome-wide association study (GWAS) linked LNX2 to weight gain in cattle [67] and another study identified LNX2 as a growth-related quantificative trait locus in the Chinese mitten crab [68]. A closer analysis of organ function outside the CNS may clarify the basis for the decreased weight observed in in LNX1/2 DKO mice.…”
Section: Mammalian Lnx1 and Lnx2mentioning
confidence: 99%
“…Genome-wide association studies (GWAS) are robust statistical tools are that broadly identify candidate genes with significant SNPs involved in production traits [14][15][16], growth traits [17,18], carcass quality traits and fertility traits [19,20]. In beef cattle, various SNPs, genes, and haplotype blocks have been found to associate with growth, however the current GWAS-based studies focus mainly on only one growth parameter [21], such as the weaning size [22], yearling weight or stature upon slaughter [23]. Furthermore, loci controlling growth traits may be variable in different growth stages, and some loci may control traits throughout the lifetime of the animal [24].…”
Section: Introductionmentioning
confidence: 99%